Role of badger setts in life of other carnivores - Sidorchuk , Natalia V.; Maslov , Michail V.; Rozhnov , Vyacheslav V. (Studia Ecologiae et Bioethicae, 2015)
A study of interspecific interactions of European (Meles meles) and Asian (M. leucurus) badgers with other carnivores at badger setts was carried out in Darwin Reserve (European part of Russia) and in Ussuriisk Reserve (Russian Far East) in 2006-2011. We used camera traps for the registration of visits of carnivore mammals to the badger setts. Overall, 11 species were recorded. In both reserves, badger setts attract carnivore species during the whole year. Some predators visit badger setts regularly. The visitors can be divided into two groups: species searching shelter, or searching prey. The first group includes raccoon dog Nyctereutes procyonoides and red fox Vulpes vulpes. Raccoon dog was the most frequent visitor in both study areas (34 visits in Darwin reserve and 73 in Ussuriisk reserve). The second group includes lynx Lynx lynx and wolf Canis lupus in Darwin reserve and Asiatic black bear Ursus thibetanus, brown bear U. arctos, yellow-throated marten Martes flavigula aterrima and lynx Lynx lynx in Ussuriisk reserve. Smaller predators are also included into the second group because they can find prey at badger setts too: leopard cat Prionailurus bengalensis euptilura, sable Martes zibellina and Siberian weasel Mustela sibirica in Ussuriisk reserve and European pine marten Martes martes in Darwin reserve. No cases of aggressive interactions between the badgers and the visitors were recorded. But we noted two cases of change of sett owners and one case when raccoon dog removed dead badger cubs from the sett.